Mechanical and chemical behavior of calcium sulfoaluminate cements obtained from industrial waste - Gallardo H., M.; Almanza R., J. M.; Cortés H., D. A.; Escobedo B., J. C. (Revista ALCONPAT, 2016)
A calcium sulfoaluminate clinker was synthesized calcining a mixture of fly ash, fluorogypsum, aluminum slag, and calcium carbonate at 1250 ºC. The clinker was mixed with 15, 20, or 25% e.p. of CaSO4·½H2O. The pastes were prepared with a water/cement ratio of 0.5. Compression resistance of cements cured in potable water and corrosive mediums at 40 ºC was evaluated. The cements cured in potable water developed compressive strengths of 38-39 MPa; those immersed in corrosive mediums showed a decrease in this property after the chemical attack. Ettringite was the main product of hydration. The degradation of the cements by chemical attack was due to a decalcification and dealumination of the pastes.